2019
DOI: 10.1002/ijc.32483
|View full text |Cite
|
Sign up to set email alerts
|

A novel lncRNA‐LINC01116 regulates tumorigenesis of glioma by targeting VEGFA

Abstract: Brain glioma is the most common malignant tumor of the central nervous system, and one of the leading causes of death in patients with intracranial tumors. The clinical outcome of glioma is usually poor due to abundant vascularity, fast growth and susceptibility of invasion to normal brain tissues. Our microarray study showed that lncRNA‐LINC01116 was significantly upregulated in glioma tissues and played an important role in cell proliferation, cycle, migration, invasion and angiogenesis. In addition, vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 37 publications
(68 reference statements)
2
57
0
Order By: Relevance
“…Three overlapping upregulated lncRNAs and three overlapping downregulated lncRNAs were randomly selected to verify the integrated analysis results. 23 In the current study, this is the first direct detection of the effect of LINC01116 on EMT process. Higher levels of LINC01116 were associated with shorter overall survival time (G; P = .017) and relapse-free survival time (H; P = .14).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Three overlapping upregulated lncRNAs and three overlapping downregulated lncRNAs were randomly selected to verify the integrated analysis results. 23 In the current study, this is the first direct detection of the effect of LINC01116 on EMT process. Higher levels of LINC01116 were associated with shorter overall survival time (G; P = .017) and relapse-free survival time (H; P = .14).…”
Section: Discussionmentioning
confidence: 77%
“…Higher levels of LINC01116 were associated with shorter overall survival time (G; P = .017) and relapse-free survival time (H; P = .14). 23 We interpret that LINC01116 could contribute to promoting EMT process by positively regulating VEGF. *P < .05.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, LINC01116 was reported to overexpressed and contributed to the progression of nasopharyngeal carcinoma, gastric cancer, osteosarcoma, glioma, epithelial ovarian cancer and head and neck squamous cell carcinoma. [17][18][19][20][21][22][23] However, there is little knowledge on the role of LINC01116 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01116 was found to promote the proliferation and migration of osteosarcoma cells through targeting miR-520a-3p and upregulating IL6R via the Jak-stat signaling pathway, 64 and was reported to promote epithelial ovarian cancer progression through regulating cell apoptosis. 23 In addition, LINC01116 was identified to regulates tumorigenesis of glioma by targeting vascular endothelial growth factor A (VEGFA), 22 and LINC01116 was shown to promote gastric cancer cell invasion and migration by positively interacting with lncRNA CASC11. 20 A recent study showed that LINC01116 contributed to gefitinib resistance in NSCLC cells by regulating IFI44 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation